Film for concrete wet curing having biodegradability

By using films with high content of biodegradable resin, the problems of existing plastic films being damaged and bleeding-prone additives under strong alkaline environments are solved, and the film is efficient, environmentally friendly and reusable wet-curing effect is achieved.

JP2025057798APending Publication Date: 2025-04-09MKV ADVANCE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023167549
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

The existing plastic films used for wet curing of concrete are damaged in a strong alkaline environment, difficult to reuse, and contain additives that are prone to bleeding, affecting the adhesive strength.

Method used

A film consisting of biodegradable resin is used to reduce the use of bleeding-prone components, ensure that the biodegradable resin in the membrane accounts for 80% or more of the total weight, and the additives that do not degrade in the short term account for less than 5%.

Benefits of technology

It is realized that the membrane is not easy to detach during the concrete wet curing process, reduces waste, and improves the working efficiency and environmental friendliness of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025057798000001
    Figure 2025057798000001
Patent Text Reader

Abstract

To provide a film for concrete wet curing which has biodegradability while having high workability, and does not generate waste.SOLUTION: A film used for wet curing a concrete contains 80 wt.% or more of a biodegradable resin, and 0 to 20 wt.% of compounds which are not decomposed in a short period of time, based on the total weight of the film, wherein a content of a compound which does not naturally exist among the compounds which are not decomposed in the short period of time is 0 to 5 wt.%, and a content of a compound which is bleed out with lapse of time among the compounds which are not decomposed in the short period of time is less than 0.2 wt.%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biodegradable film suitable for wet concrete curing and having excellent biodegradability, more specifically, to a film for wet concrete curing that suppresses bleed-out and has excellent workability. [Background technology]

[0002] Generally, concrete needs to be cured until it is sufficiently hardened after being poured. The quality of curing has a large impact on the properties of the concrete after hardening, but during concrete curing, sunlight and rising outside temperatures can cause the moisture in the concrete to evaporate, causing cracks in the concrete. To go into more detail, concrete curing uses the heat source generated by the hydration reaction of the concrete to allow it to dry naturally and harden, but in summer, rising outside temperatures and sunlight make it very easy for the moisture in the concrete to evaporate, accelerating the drying process and causing it to dry unevenly in parts, making it more susceptible to cracks.

[0003] In addition, the rapid drop in concrete temperature in winter has a negative effect on concrete curing, so there is a demand for effective curing aids that can prevent concrete cracking due to sunlight in summer and suppress rapid temperature drops in winter.

[0004] In response to these issues, attempts have been made to carry out the curing process by pouring a concrete foundation, covering it with a moist curing film to block sunlight, and then spraying water from underneath the film to prevent moisture from evaporating, as exemplified in JP 2002-256705 A (Patent Document 1).

[0005] The films used in this process are ordinary plastic films, but because strong alkaline substances such as calcium hydroxide precipitate and adhere during the concrete wet curing process, the films must be washed before they can be reused for the same or a different purpose after use. Even if the films are washed, the strong alkaline substances damage the film itself, significantly reducing its strength, and so they must be disposed of as waste.

[0006] In addition, the plastic films used in this process often contain various additives to improve formability and weather resistance, but these components may bleed out over time. The films used in the wet concrete curing process are generally attached to each other and to the edge of the concrete with tape to prevent the film from shifting or falling off due to wind, but if the bleed-out components of the plastic film are present on the surface, the adhesive strength of the tape cannot be sufficient and it may fall off due to stress. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2002-256705 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a film for wet curing of concrete which has high workability, is biodegradable and does not produce waste. [Means for solving the problem]

[0009] In order to solve the above problems, the inventors discovered that by using a biodegradable resin as the main component and minimizing the amount of components that bleed out, it is possible to reduce waste emissions while maintaining high workability, and thus completed the present invention. That is, the present invention provides: [1] Based on the total weight of the film, the film contains 80% by weight or more of biodegradable resin and 0 to 20% by weight of a compound that does not decompose in the short term; Among the compounds that do not decompose in a short period of time, the content of compounds that do not exist in nature is 0 to 5% by weight, A film for use in wet curing of concrete, wherein the content of compounds that bleed out over time among the compounds that do not decompose in the short term is less than 0.2% by weight. [2] The film according to [1], having a thickness of 0.01 mm to 0.1 mm. [3] The film according to [1] or [2], containing 90% or more by weight of a biodegradable resin. Regarding. Effect of the Invention

[0010] By using the film for wet curing concrete of the present invention, it is possible to prevent the film from coming off during the wet curing process of concrete, and also to suppress the discharge of waste, which has been a problem in the past. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below, but the present invention is not limited to the above embodiment and can be modified and practiced in various ways within the scope of the gist of the present invention. In this specification, when the expression "~" is used, it is used as an expression including the numerical values ​​or physical property values ​​before and after it.

[0012] In the present invention, the film used for wet curing of concrete (hereinafter also referred to as "film for wet curing of concrete") is a film used to prevent the evaporation of water sprayed on the top of concrete in order to ensure the required qualities of concrete, such as strength, durability, and watertightness, and to ensure the moisture necessary for hardening for a certain period of time after pouring. In addition, the film for wet curing of concrete of the present invention is a film mainly composed of a biodegradable resin that is decomposed into water and carbon dioxide by the action of microorganisms, and the film for wet curing of concrete of the present invention may be single-layered or multi-layered. The resins and other components constituting the film for wet curing concrete of the present invention will be described in detail below.

[0013] (1) Biodegradable resin The biodegradable resin in the present invention is not particularly limited as long as it is a resin that has the property of being decomposed into water and carbon dioxide by the action of microorganisms, but it is desirable for the resin to have sufficient strength as a film, the property that decomposition is not accelerated during the moist curing process, and the property that it quickly decomposes in the soil or in various decomposition processes after the period of use.

[0014] As the biodegradable resin used in the present invention, an aliphatic aromatic polyester resin, an aromatic polyester resin, or a lactic acid-based polyester resin can be suitably used. By using these resins as the main components, the time for hydrolysis by moisture and microbial decomposition by microorganisms is moderate, decomposition is not accelerated during the moist curing process, and after the usage period, the film has the property of being quickly decomposed in soil or in various decomposition processes, and the film strength during the usage period can be made favorable. The content of the biodegradable resin is preferably 80% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and particularly preferably 99% by weight or more. Any biodegradable resin composition may be combined within these ranges.

[0015] Aliphatic aromatic polyester resin Specific examples of the aliphatic aromatic polyester resin in the present invention include those having, as constituent components, an aliphatic diol unit represented by the following formula (1), an aliphatic dicarboxylic acid unit represented by the following formula (2), and an aromatic dicarboxylic acid unit represented by the following formula (3). -OR 1 -O- (1) (In the formula, R1 represents a divalent aliphatic hydrocarbon group having 2 or more carbon atoms, preferably 2 to 10 carbon atoms, or a divalent alicyclic hydrocarbon group having 3 or more carbon atoms, preferably 3 to 10 carbon atoms, and when copolymerized, is not limited to one type. -OC-R 2 -CO- (2) (In the formula, R 2 represents a direct bond, a divalent chain aliphatic hydrocarbon group having 1 or more carbon atoms (preferably 1 to 10 carbon atoms) and / or a divalent alicyclic hydrocarbon group having 3 or more carbon atoms (preferably 3 to 10 carbon atoms), and when copolymerized, is not limited to one type. -OC-R 3 CO- (3) (In the formula, R 3 represents a divalent aromatic hydrocarbon group, and when copolymerized, the number of types is not limited to one.

[0016] The diol component that gives the diol unit of formula (1) usually has 2 to 10 carbon atoms, and examples thereof include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, etc. Among them, diols having 2 to 4 carbon atoms are preferred, ethylene glycol and 1,4-butanediol are more preferred, and 1,4-butanediol is particularly preferred.

[0017] The dicarboxylic acid component that gives the dicarboxylic acid unit of formula (2) usually has 2 to 10 carbon atoms, and examples thereof include succinic acid, adipic acid, suberic acid, sebacic acid, dodecanedioic acid, etc. Among these, succinic acid or adipic acid is preferred.

[0018] Examples of aromatic dicarboxylic acid components that give the aromatic dicarboxylic acid unit of formula (3) include terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, among which terephthalic acid and isophthalic acid are preferred, and terephthalic acid is particularly preferred.Furthermore, aromatic dicarboxylic acids in which a part of the aromatic ring is substituted with a sulfonate salt can be mentioned.In addition, two or more kinds of aliphatic dicarboxylic acid components, aliphatic diol components, and aromatic dicarboxylic acid components can be used respectively.

[0019] The aliphatic aromatic polyester resin of the present invention may contain an aliphatic oxycarboxylic acid unit. Specific examples of the aliphatic oxycarboxylic acid that gives the aliphatic oxycarboxylic acid unit include lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 6-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, and mixtures thereof. Furthermore, these may be lower alkyl esters or intramolecular esters. When these have optical isomers, they may be D-, L- or racemic, and may be in the form of solid, liquid or aqueous solution. Among these, lactic acid or glycolic acid is preferred. These aliphatic oxycarboxylic acids may be used alone or in a mixture of two or more.

[0020] The amount of the aliphatic oxycarboxylic acid is preferably 0 to 30 mol %, more preferably 0.01 to 20 mol %, based on the total components constituting the aliphatic aromatic polyester resin.

[0021] The melt flow rate (MFR) of the aliphatic aromatic polyester resin in the present invention, when measured at 190°C under a load of 2.16 kg, is preferably 0.1 to 100 g / 10 min, more preferably 0.1 to 50 g / 10 min, and particularly preferably 0.1 to 30 g / 10 min.

[0022] Specific examples of such aliphatic aromatic polyester resins include "Ecoflex" manufactured by BASF and "EnPol" manufactured by S-EnPol.

[0023] <Aliphatic polyester resin> As the aliphatic polyester resin, an aliphatic polyester resin containing an adipic acid unit as a dicarboxylic acid unit, an aliphatic polyester resin not containing an adipic acid unit as a dicarboxylic acid unit, or the like can be used. The aliphatic polyester resin that is a component of the aliphatic polyester resin that can be used in the present invention is preferably an aliphatic polyester resin mainly composed of aliphatic diol units and aliphatic dicarboxylic acid units. Here, the term "main component" means that the aliphatic diol units and aliphatic dicarboxylic acid units account for 70 mol % or more, preferably 80 mol % or more, and more preferably 90 mol % or more of the total monomer units that constitute the aliphatic polyester (100 mol %).

[0024] Specifically, the aliphatic polyester resin is, for example, composed of a chain aliphatic and / or alicyclic diol unit represented by the following formula (4) and a chain aliphatic and / or alicyclic dicarboxylic acid unit represented by the following formula (5). -OR 4 -O- (4) (In the formula, R 4 represents a divalent chain aliphatic hydrocarbon group and / or a divalent alicyclic hydrocarbon group. In the case of copolymerization, two or more R 4 may be included.) -OC-R 5 -CO- (5) (In the formula, R 5 represents a divalent chain aliphatic hydrocarbon group and / or a divalent alicyclic hydrocarbon group. In the case of copolymerization, two or more R 5 may be included.) In the above formulas (4) and (5), the term "divalent linear aliphatic hydrocarbon group and / or divalent alicyclic hydrocarbon group" means that both a divalent linear aliphatic hydrocarbon group and a divalent alicyclic hydrocarbon group may be included. In the following, "linear aliphatic and / or alicyclic" may be abbreviated to simply "aliphatic".

[0025] The aliphatic polyester resin contains 1,4-butanediol units as an essential component of the diol units of the above formula (4). The content of the 1,4-butanediol units is preferably 30 to 60 mol %, particularly preferably 40 to 50 mol %, based on the total monomer units constituting the aliphatic polyester resin (100 mol %). The diol unit other than the 1,4-butanediol unit is not particularly limited, but is preferably an aliphatic diol unit having 3 to 10 carbon atoms, and more preferably an aliphatic diol unit having 4 to 6 carbon atoms. Specific examples include 1,3-propanediol and 1,4-hexanedimethanol. Two or more diol components that provide the aliphatic diol unit may be used.

[0026] The aliphatic polyester resin further contains a succinic acid unit as a dicarboxylic acid unit as an essential component. Furthermore, when the aliphatic polyester resin contains adipic acid as an essential component of the dicarboxylic acid unit, the content of the adipic acid unit is preferably 0.5 to 20 mol %, and more preferably 1 to 15 mol %, based on the total monomer units constituting the aliphatic polyester resin (100 mol %). The dicarboxylic acid unit other than the succinic acid unit and the adipic acid unit is not particularly limited, but is preferably an aliphatic dicarboxylic acid unit having 2 to 10 carbon atoms, and particularly preferably an aliphatic dicarboxylic acid unit having 4 to 8 carbon atoms. Specific examples include suberic acid, sebacic acid, and dodecanedioic acid. Two or more kinds of dicarboxylic acid components that give the aliphatic dicarboxylic acid unit can be used.

[0027] Furthermore, the aliphatic polyester resin may contain an aliphatic oxycarboxylic acid unit. Specific examples of the aliphatic oxycarboxylic acid that gives the aliphatic oxycarboxylic acid unit include lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 6-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, and the like, or lower alcohols or intramolecular esters thereof. When optical isomers exist in these, they may be any of D-form, L-form, or racemic form, and may be in any form of solid, liquid, or aqueous solution. Among these, lactic acid and glycolic acid are particularly preferred. These aliphatic oxycarboxylic acids can be used alone or in combination of two or more. The content of the aliphatic oxycarboxylic acid unit is preferably 0 to 30 mol %, more preferably 0.01 to 20 mol %, and particularly preferably 0.01 to 10 mol %, based on the total monomer units constituting the aliphatic polyester resin (100 mol %). Specific examples of such aliphatic polyester resins include "GSPla" manufactured by Mitsubishi Chemical Corporation and "Bionolle" manufactured by Showa Denko KK.

[0028] <Lactic acid-based polyester resin> The lactic acid-based polyester resin usable in the present invention may be a homopolymer or copolymer of L-lactic acid, D-lactic acid, DL-lactic acid, or a mixture thereof, lactide, etc. The lactic acid-based polyester resin may be produced from these raw materials by direct dehydration condensation or ring-opening polymerization of lactide, but the production method is not particularly limited. In addition, hydroxycarboxylic acids other than lactic acid, aliphatic polyhydric alcohols, aliphatic polybasic acids, etc. may be copolymerized to the extent that the properties of the lactic acid-based polyester resin are not impaired. Specific examples of such lactic acid-based polyester resins include "Ingeo Biopolymer" manufactured by Nature Works and "REVODE" manufactured by Zhejiang Hisheng Biomaterials Co., Ltd. Furthermore, the lactic acid-based polyester resin thus produced may be mixed in advance with another aliphatic polyester resin or an aliphatic aromatic polyester resin to be used as a raw material. A specific example of such a mixed resin with a lactic acid-based polyester resin is "Ecovio F Blend C2224" manufactured by BASF Japan Ltd.

[0029] (2) Compounds that do not decompose in the short term In this specification, the term "compounds that do not decompose in the short term" broadly refers to compounds that do not decompose or that decompose over a fairly long period of time. More specifically, the term "compounds that do not decompose in the short term" refers to compounds that do not decompose naturally at least during the use of the film for wet curing of concrete of the present invention, and do not decompose easily even in a decomposition treatment after use. The term "compounds that do not decompose in the short term" basically does not have the property of being decomposed into water and carbon dioxide by the action of microorganisms, like the biodegradable resin used in the present invention. As the compound that does not decompose in the short term that can be used in the present invention, various additives known in the art can be blended. Examples of such additives include crystal nucleating agents, antioxidants, antiblocking agents, inorganic fillers, slip agents, ultraviolet absorbers, plasticizers, heat stabilizers, colorants, light stabilizers, flame retardants, release agents, antistatic agents, antifogging agents, surface wettability improvers, incineration aids, pigments, lubricants, dispersants, various surfactants, hydrolysis inhibitors, etc. These may be used alone or in combination of two or more.

[0030] The content of these compounds that do not decompose in the short term is preferably 0 to 20% by weight, more preferably 0 to 10% by weight, further preferably 0 to 5% by weight, and particularly preferably 0 to 1% by weight, based on the total weight of the film. If the content is within the above range, not only will the strength of the film decrease, but the amount of components remaining after decomposition of the biodegradable resin will increase, which is undesirable since it will increase the burden on the environment.

[0031] Among the compounds that do not decompose in the short term, the ratio of compounds that do not exist in nature is preferably 0 to 5% by weight, more preferably 0 to 1% by weight, and particularly preferably 0 to 0.5% by weight, based on the total weight of the film. Since it is expected that the film for wet curing concrete of the present invention will be buried in the ground as one of the decomposition processes, it is undesirable for substances that do not exist in nature to remain, and it is desirable to keep the content within the above range.

[0032] Representative examples of compounds that do not decompose in the short term and that can be used in the present invention include the following:

[0033] Anti-blocking Agent Examples of the antiblocking agent include saturated fatty acid amides having 6 to 30 carbon atoms, saturated fatty acid bisamides (e.g., stearic acid amide, stearic acid bisamide), methylol amide, ethanol amide, natural silica, synthetic silica, synthetic zeolite, talc, etc., and one of these may be used alone or two or more may be used in combination.

[0034] inorganic filler Inorganic fillers that can be used in the present invention include silica, mica, talc, titanium oxide, calcium carbonate, diatomaceous earth, allophane, bentonite, potassium titanate, zeolite, sepiolite, smectite, kaolin, kaolinite, glass, limestone, carbon, wollastonite, calcined perlite, silicates such as calcium silicate and sodium silicate, aluminum oxide, magnesium carbonate, hydroxides such as calcium hydroxide, ferric carbonate, zinc oxide, iron oxide, aluminum phosphate, barium sulfate, and the like. Among these, one type may be used alone, or two or more types may be mixed and used. As described above, the inorganic filler is preferably a substance that exists in nature, particularly a substance that exists in the soil, and talc or the like can be suitably used.

[0035] Slip Agent Examples of the slip agent include unsaturated fatty acid amides and unsaturated fatty acid bisamides made of unsaturated fatty acids having 6 to 30 carbon atoms, and erucic acid amide and erucic acid bisamide are preferred.

[0036] Coloring agent As the colorant, there can be used colorants that are usually used in agricultural mulch films, such as carbon black, titanium oxide, etc. The colorant may be used as it is, or may be added as a master batch.

[0037] Antioxidants Antioxidants include BHT, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 3,3',3",5,5',5"-hexa-tert-butyl-α,α',α"-(mesitylene-2,4,6-triyl)tri-p-cresol, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethylphenylpropionate, and 1,3,5-trimethylphenylpropionate. 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, Calcium diethyl bis[{3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl}methyl]phosphonate, Bis(2,2'-dihydroxy-3,3'-di-tert-butyl)methyl hindered phenol antioxidants such as N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl)-4-hydroxyphenyl]propionamide, and n-octadecyl 3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate; tridecyl phosphite; diphenyl decyl phosphite; tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbis ... Examples of such antioxidants include phosphorus-based antioxidants such as phosphonite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphorous acid, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite; lactone-based antioxidants such as a reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and xylene; sulfur-based antioxidants such as dilauryl thiodipropionate and distearyl thiodipropionate; and mixtures of two or more of these antioxidants.

[0038] Stabilizer Stabilizers include fatty acid metal salts. The fatty acid component of the fatty acid metal salt is a chain-like carboxylic acid having a carboxyl group, usually having 6 to 30 carbon atoms, which may be linear or branched, and may have only saturated bonds or unsaturated bonds. Specific examples of fatty acids include caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, montanic acid, palmitoleic acid, oleic acid, eicosenoic acid, erucic acid, elaidic acid, trans-11 eicosenoic acid, trans-13 docosenoic acid, linoleic acid, linolenic acid, ricinoleic acid, and erucic acid.

[0039] On the other hand, the metal atom is preferably an atom of Groups 1A, 2A, 2B, and 3B of the periodic table, and preferred examples include sodium, potassium, calcium, magnesium, barium, aluminum, and zinc.

[0040] Examples of fatty acid metal salts include calcium stearate, magnesium stearate, barium stearate, aluminum stearate, zinc stearate, calcium laurate, magnesium laurate, aluminum laurate, and sodium montanate. These may be used alone or in combination of two or more. Among these, calcium stearate, magnesium stearate, aluminum stearate, calcium laurate, magnesium laurate, and aluminum laurate are preferred.

[0041] Dispersants The dispersant may be an ester wax such as montan wax.

[0042] UV absorbers As the ultraviolet absorbent, among ultraviolet absorbents such as benzophenone-based, benzotriazole-based, triazine-based, salicylic acid-based, and cyanoacrylate-based ultraviolet absorbents, benzotriazole-based ultraviolet absorbents are preferred, and specific examples thereof include 2-[5-chloro(2H)-benzotriazole-2-yl]-4-methyl-6-(tert-butyl)phenol, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxy-phenol.

[0043] Light stabilizers Examples of the light stabilizer include bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, 2-(3,5-di-t-butyl-4-hydroxyphenyl)-2-n-butyl-bis(2,2,6,6-tetramethyl-4-piperidyl)malonate, 2-(3,5-di-t-butyl-4-hydroxyphenyl)-2-n-butyl-bis(1,2,2,6,6-penta ... 2-(3,5-di-t-butyl-4-hydroxybenzyl)-2-n-butyl-bis(1,2,2,6,6-pentamethyl-4-piperidyl)malonate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, mixed(2,2,6,6-tetramethyl-4-piperidyl / tridecyl)-1,2,3,4-butanetetracarboxylate silane, mixed (1,2,2,6,6-pentamethyl-4-piperidyl / tridecyl)-1,2,3,4-butane tetracarboxylate, mixed {2,2,6,6-tetramethyl-4-piperidyl / β,β,β',β'-tetramethyl-3,9-[2,4,8,10-tetraoxaspiro[5.5]undecane]diethyl}-1,2,3,4-butane tetracarboxylate, mixed {1,2,2,6,6-pentamethyl-4-piperidyl / β,β,β',β'-tetramethyl-3,9-[2,4,8,10-tetraoxaspiro[5.5]undecane]diethyl}-1,2,3,4-butane tetracarboxylate xylates, 1,2-bis(3-oxo-2,2,6,6-tetramethyl-4-piperidyl)ethane, 1-(3,5-di-t-butyl-4-hydroxyphenyl)-1,1-bis(2,2,6,6-tetramethyl-4-piperidyloxycarbonyl)pentane, poly[1-oxyethylene(2,2,6,6-tetramethyl-1,4-piperidyl)oxysuccinyl], poly[2-(1,1,4-trimethylbutylimino)-4,6-triazinediyl-(2,2,6,6-tetramethyl-4-piperidyl)iminohexamethylene-(2,2,6,6-tetramethyl-4-piperidyl)imino], N,N'-bis(3-amino propyl)ethylenediamine-2,4-bis[N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino]-6-chloro-1,3,5-triazine condensate and its N-methyl compound, polycondensate of succinic acid and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine, poly[{6-((1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{((2,2,6,6-tetramethyl-4-piperidyl)imino}], and the like.

[0044] Plasticizer The plasticizer used in the present invention is not particularly limited, but is particularly preferably a biodegradable one, for example, acetylated citric acid esters such as acetyl tri-n-butyl enoate or acetyl triethyl citrate, acetylated monoglycerides, esters of alkyl glyceryl ethers or esters of alkylene oxide adducts of alkyl glyceryl ethers, esters of polycarbonate diols and aromatic monocarboxylic acids, condensed polycyclic aromatic monocarboxylic acids, etc.

[0045] other natural products Furthermore, the film for wet curing concrete of the present invention can be blended with biodegradable resins other than those exemplified above, as well as natural products, such as polycaprolactone, polyamide, polyvinyl alcohol, cellulose esters, etc., as well as fine powders of animal / plant substances, such as starch, cellulose, paper, wood flour, chitin / chitosan, coconut shell powder, walnut shell powder, etc., within the scope of not impairing the effects of the present invention.

[0046] Among the above-mentioned compounds that do not decompose in the short term, compounds that do not exist in nature include, for example, organic substances that are not biodegradable, such as high molecular weight polymers and low molecular weight organic compounds produced by chemical synthesis, including polyethylene, polypropylene, polyethylene terephthalate, etc. Similarly, inorganic substances include inorganic compounds that are produced only by chemical synthesis. Among the above-mentioned compounds that do not decompose in the short term, compounds present in nature include, for example, minerals present in the soil or on the surface of the earth, such as silica, mica, talc, titanium oxide, calcium carbonate, diatomaceous earth, allophane, bentonite, potassium titanate, zeolite, sepiolite, smectite, kaolin, etc. Compounds present in nature also include carbon black (which is produced industrially, but is itself a carbon particle and exists in nature).

[0047] (3) Compounds that bleed out over time In this specification, the term "compounds that bleed out over time" refers to compounds that precipitate from within the film to the film surface over time due to the concentration gradient within the film. Examples of such compounds include antiblocking agents, slip agents, light stabilizers, plasticizers, and ultraviolet absorbers. These compounds that bleed out over time form a film when precipitated on the film surface, and when a tape is applied to fix the film, this film prevents direct adhesion to the film surface. For the above reasons, it is desirable that the proportion of these compounds is less than 0.2% by weight.

[0048] Details of the antiblocking agent, slip agent, light stabilizer, plasticizer, and ultraviolet absorber used as compounds that bleed out over time are the same as those described above for the compounds that do not decompose in the short term.

[0049] The thickness of the film for wet curing concrete of the present invention is preferably 0.01 mm to 0.1 mm, more preferably 0.01 mm to 0.05 mm, and particularly preferably 0.015 mm to 0.02 mm. By making the film thickness 0.01 mm or more, the film can be more stably formed, and the strength can be prevented from being insufficient when used in work, etc. Furthermore, by making the film thickness 0.1 mm or less, the decomposition in the soil or other methods after use can be prevented from being insufficient.

[0050] The biodegradable resin composition (i.e., a composition containing a biodegradable resin, a compound that does not decompose in a short period of time, etc.) used in the present invention can be kneaded by a method generally used for kneading resin compositions. Specifically, pellets, powder, solid pieces, etc. can be dry-mixed in a Henschel mixer or ribbon mixer, and then fed to a known melt kneader such as a single-screw or twin-screw extruder, a Banbury mixer, a kneader, or a mixing roll for melt kneading. Suitable methods for forming the biodegradable resin composition into a film include extrusion molding in which a film extruded through a T-die using an extruder is cooled and solidified using a cast roll, and molding using an inflation molding machine. EXAMPLES

[0051] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0052] Bleed-out determination The film bleed-out was evaluated according to JISK 6768:1999, "Plastics - Films and sheets - Wet tension test method," under two conditions: the film was washed within one hour of molding, and the film was left at rest at 25°C for 20 days to accelerate the bleed-out. Specifically, the wet tension was evaluated according to the following procedure. Measurements are performed in a standard laboratory atmosphere (see JIS K 7100) with a temperature of 23°C and a relative humidity of 50%. The test piece is placed on the hand coater substrate, a few drops of the test mixture are placed on the test piece, and the test piece is immediately spread by pulling the wire bar. If a cotton swab or brush is used to spread the test mixture, the liquid should be spread to at least 6 cm. 2 The liquid should be quickly spread over an area of ​​at least 10 mm. The amount of liquid should be enough to form a thin layer without pooling. The wetting tension is judged by observing the liquid film of the test mixed liquid in a bright place and observing the state of the liquid film after 2 seconds. If the liquid film does not break and remains in the same state as when it was applied for 2 seconds or more, it is considered to be wetting. If the wetting is maintained for 2 seconds or more, proceed to a mixed liquid with the next higher surface tension, and conversely, if the liquid film breaks in 2 seconds or less, proceed to a mixed liquid with the next lower surface tension. Repeat this process to select a mixed liquid that can accurately wet the surface of the test piece in 2 seconds.

[0053] Tape peel strength The tape peel strength of the film was evaluated according to the following procedure. A Nichiban cellophane tape measuring 18 mm wide and 120 mm long is applied to the test piece, and a 2 kg pressure roller is used to press it back and forth twice without applying force. The tape is then cut off within 5 mm from the outside. One end of the tape is then partially peeled off, and the peeled tape and film end face are placed on an autograph, and a peel test is performed with a load cell of 100 g and a peel speed of 100 mm / min. From the obtained peel strength data, the points where the peel strength is stable, excluding the initial rise in peeling, are extracted and the average value is recorded. The above operation is performed three times, and the average value is taken as the tape peel strength.

[0054] [Raw materials used] Aliphatic aromatic polyester (A): BASF product name "Ecoflex" (biodegradable resin) Aliphatic aromatic polyester (B): Mitsubishi Chemical Corporation, product name "BioPBS FZ91PB" (biodegradable resin) Slip agent (C): Mitsubishi Chemical Corporation, product name "Slipax E" (Compounds that do not exist in nature and bleed out) Inorganic filler (talc) (D): Made by Nippon Mistron Co., Ltd., product name "ImerFlex 850JS" (a compound that exists in nature and does not bleed out) Ultraviolet absorber (E): BASF Japan product name "Tinuvin 3226" (a compound that does not exist in nature and bleeds out) Colorant (F): Mitsubishi Chemical Corporation product name "#45L" (carbon black) (Naturally occurring compounds that do not bleed out)

[0055] [Examples 1 to 6, Comparative Examples 1 to 6] The slip agent, inorganic filler, UV absorber, and colorant were mixed in advance with the aliphatic polyester in fixed amounts and melt-kneaded using a twin-screw extruder to prepare a master batch. These were then dry-blended in the form of pellets using the compositions shown in Table 1. The cylinder and die temperatures were set to the melting temperature of the aliphatic polyester + 40°C, and a film with a thickness of 18 μm was molded using a Modern inflation molding machine.

[0056] The obtained film was evaluated by the above-mentioned test methods, and the results are shown in Table 1.

[0057] [Table 1]

[0058] From the results of the Examples and Comparative Examples, in Examples 1 to 6, in which the compound that bleeds out is less than 0.2% by weight, the change in the wet tension of the film surface over time is small, i.e., the film bleeds out less, so the tape peel strength value is unlikely to become small, while in Comparative Examples 1 to 6, in which the compound that bleeds out is 0.2% by weight or more, the change in the wet tension of the film surface over time is large, i.e., the film bleeds out a lot, so the tape peel strength value is less than half of that before the bleed-out. From this, it can be said that the wet concrete curing film of the present invention can maintain good tape adhesive strength even after a long time has passed since its production.

Claims

1. Based on the total weight of the film, the film contains 80% by weight or more of a biodegradable resin and 0 to 20% by weight of a compound that does not decompose in the short term; Among the compounds that do not decompose in a short period of time, the content of compounds that do not exist in nature is 0 to 5% by weight, A film for use in wet curing of concrete, wherein the content of compounds that bleed out over time among the compounds that do not decompose in the short term is less than 0.2% by weight.

2. The film of claim 1 having a thickness of 0.01 mm to 0.1 mm.

3. 3. The film according to claim 1, which contains 90% by weight or more of a biodegradable resin.

Citation Information

Patent Citations

  • Curing protection device with function to sprinkle water over concrete and curing protection sheet for use therewith

    JP2002256705A